Intraosseus administration of an ultrasound contrast agent in a case of pediatric blunt abdominal trauma - Tobias Kummer; Graciela Maldonado; R. Ross Reichard (Elsevier, 2022)
Adding an ultrasound contrast agent to the Focused Assessment with Sonography in Trauma (FAST) exam can substantially improve the diagnostic accuracy of identifying solid organ injuries and rapidly identify significant organ lacerations and active intraperitoneal hemorrhage. The standard recommendations are to use a 20g peripheral IV for administration to prevent microbubble breakage associated with high infusion pressures. In time-critical trauma resuscitations however, rapid vascular access often necessitates the use of intraosseous catheters (IO). We describe the first use of IO access to successfully administer an ultrasound contrast agent in a critically injured 16 month-old toddler. The cFAST exam identified a liver laceration and provided superior diagnostic information compared the non-contrast abdominal CT obtained at an outside facility.